Pengaruh Debt to Asset Ratio dan Ukuran Perusahaan Terhadap Harga Saham pada Perusahaan Subsektor Tekstil dan Garmen Periode 2021-2023 - Zakiyya, Tiara Putri; Mahpudin, Endang (Peneliti.net, 2026)
The intense competition in the capital market, along with the economic stability recovery period in Indonesia during 2021–2023, has become a point of interest for researchers to conduct this study. This research aims to examine the influence of the debt to asset ratio and firm size on stock prices in textile and garment subsector companies. The analytical method used in this study is a quantitative approach by conducting classical assumption tests, hypothesis testing, and determining the coefficient of determination. The results show that the debt to asset ratio does not have a significant effect on stock prices, while firm size has a significant negative effect on stock prices. However, when tested simultaneously, the debt to asset ratio and firm size together have a significant positive effect on stock prices in textile and garment companies during the 2021–2023 period.